2006
DOI: 10.1007/s11430-006-8310-6
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal drought effects on carbon sequestration of a mid-subtropical planted forest of southeastern China

Abstract: Continuous measurement of carbon dioxide exchange using the eddy covariance (EC) technique is made at the Qianyanzhou mid-subtropical planted forest as part of the ChinaFLUX network. Qianyanzhou planted forest is affected by typical subtropical continental monsoon climate. It has plentiful water and heat resource but is in inconsistency of its seasonal distribution in the midsubtropical region, thus seasonal drought frequently occurs in this planted forest. In this study, seasonal drought effect on ecosystem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 22 publications
(27 reference statements)
0
27
0
Order By: Relevance
“…However, GPP declined during the summer depression period. Previous studies also reported that high temperatures and low soil water content might cause GPP to decline in this forest [64,65].…”
Section: Seasonal Patterns Of Bioclimatic Factors Productivity Primentioning
confidence: 56%
“…However, GPP declined during the summer depression period. Previous studies also reported that high temperatures and low soil water content might cause GPP to decline in this forest [64,65].…”
Section: Seasonal Patterns Of Bioclimatic Factors Productivity Primentioning
confidence: 56%
“…For instance, the severe drought (and heat) occurring in European countries in 2003 substantially reduced photosynthesis and respiration, GPP in particular [74] , resulting in an anomalous net C source (0.5 Pg C a −1 ) being equivalent to the 4-year net ecosystem C sequestration [75] . The water stress in the same year also reduced the C sink strength of a warm temperate coniferous forest in southern China [76] . However,Canadian studies reported that severe drought decreased both GPP and TER in an aspen forest, causing either little change or a subtle reduction in NEP [37,38] ; mild-to-moderate water stress decreased TER but had little effect on GPP, leading to an increase in NEP [38] .…”
Section: Interannual Variations Of Forest Carbon Fluxesmentioning
confidence: 95%
“…5o). The extremely hot and dry weather conditions in the 2003 summer and the effects on the ecosystem at QYZ have been found and described in detail in studies such as those by Sun et al (2006), Wen et al (2006), and Yu et al (2008).…”
Section: Meteorological Conditions and Gpp At Ground Observational Simentioning
confidence: 99%